2015
DOI: 10.1016/j.juro.2014.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Prevalence in Invasive Penile Cancer and Association with Clinical Outcome

Abstract: High risk human papillomavirus-DNA was observed in a quarter of penile cancer cases. No relevant increase in high risk human papillomavirus prevalence in recent decades was observed. The presence of high risk human papillomavirus-DNA in penile cancer confers a survival advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 28 publications
(1 reference statement)
5
66
1
1
Order By: Relevance
“…Previous studies have generally shown HPV and p16 positivity to associate with favorable prognosis (17,(21)(22)(23). Likewise, although exploratory due to the limited number of samples with alterations and events, MYC and CCND1 amplifications were both significantly associated with decreased event-free survival.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have generally shown HPV and p16 positivity to associate with favorable prognosis (17,(21)(22)(23). Likewise, although exploratory due to the limited number of samples with alterations and events, MYC and CCND1 amplifications were both significantly associated with decreased event-free survival.…”
Section: Discussionmentioning
confidence: 95%
“…[2][3][4] In circumcised men, HPV prevalence is lower than in uncircumcised men, and penile cancer is rare in populations that routinely practice circumcision. 5 Some published studies state that HPV16, 18,31,33,35,39,45,51,52,56,58,59,66, and 68 have been associated with intraepithelial neoplasia and carcinoma of the cervix. [6][7][8] The studies indicate that these types of HPV were considered primary high-risk (carcinogenic) genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…While an APOBEC signature has recently been detected in penile cancer when the HPV load was high [18], this finding was not reflected by the overall mutational load, which was not found to be significantly increased [18]. Moreover, HPV-associated penile SCCs have been shown to have a more favorable prognosis than HPV-negative tumors, which would also argue against enhanced mutagenesis and genomic instability [25,26]. In addition, the expression of APOBECs has been found to correlate only weakly with the actual APOBEC mutational signatures and HPV oncogene expression [3].…”
Section: Discussionmentioning
confidence: 96%
“…The assay can detect 15 high-risk types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 68, 73, 82), 3 putative high-risk types (26,53,66), and 6 low-risk types (6,11,42,43,44,70). DNA for the test was extracted from formalin-fixed, paraffin-embedded sections using the DNeasy Blood and Tissue Kit (Qiagen, Hilden, Germany).…”
Section: Hpv Genotypingmentioning
confidence: 99%